Analisis Akustik Target Strength Penyu Hijau (Chelonia Mydas) Melalui Pengukuran Secara Terkontrol Pada Frekuensi 200 kHz - Teddy Julyansyah; Deddy Bakhtiar; Ari Anggoro (Fakultas Perikanan dan Ilmu Kelautan Universitas 17 Agustus 1945 Cirebon, 2021)
ABSTRACT Turtles are reptiles that live in the sea and are able to migrate over long distances along the Indian Ocean, Pacific Ocean and Southeast Asia. Currently the number of turtle populations in nature has greatly decreased. This population decline is caused by natural factors and human activities that endanger the population directly or indirectly. At this time the tagging set technique (ID tag code) is a method that is often used to detect the presence of turtles by attaching tags to female turtles who are landing to lay eggs on the beach or while in captivity or the discovery of the mother turtle by fishermen. One other method that can be used to detect the presence of turtles is to use the acoustic method. The purpose of this study was to analyze the characteristics of the acoustic backscattering energy of the green turtle (Chelonia mydes) and to analyze the relationship between target strength and total body length of the green turtle (Chelonia mydas). This research was conducted in the Tapak Paderi waters pond, Bengkulu City, in August-October 2020. The average target strength (TS) value for green turtles was -48.07 dB. Based on the regression equation, the value of determination (R2) obtained is 0.78. Where this value shows that the total length of the green turtle has an effect of 78% on the average target strength (TS) value, while for 22% it is caused by other factors such as body shape, environmental factors and other factors. Based on the ANOVA test, it can be concluded that there is a relationship between the total length and the value of the target strength (TS) on the green turtle or the value of the total length has an influence on the value of the target strength (TS) on the green turtle.